2013
DOI: 10.1021/es4007228
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of Melanoma Cell Invasion and Tumor Metastasis by Microcystin-LR via Phosphatidylinositol 3-Kinase/AKT Pathway

Abstract: Recently, we have indicated that microcystin-LR, a cyanobacterial toxin produced in eutrophic lakes or reservoirs, can increase invasive ability of melanoma MDA-MB-435 cells; however, the stimulatory effect needs identification by in vivo experiment and the related molecular mechanism is poorly understood. In this study, in vitro and in vivo experiments were conducted to investigate the effect of microcystin-LR on invasion and metastasis of human melanoma cells, and the underlying molecular mechanism was also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 39 publications
4
23
0
Order By: Relevance
“…PP2A is an important enzyme which dephosphorylates Akt at these residues . The activation of Akt induced by MC‐LR owing to inhibition of PP2A has been reported by many groups, including in our previous work . In the current study, Akt activation was observed in HL7702 cells and in MC‐LR‐treated mice' livers owing to the finding that the phosphorylation level of Akt at Thr 308 and Ser 473 was significantly increased.…”
Section: Discussionsupporting
confidence: 66%
“…PP2A is an important enzyme which dephosphorylates Akt at these residues . The activation of Akt induced by MC‐LR owing to inhibition of PP2A has been reported by many groups, including in our previous work . In the current study, Akt activation was observed in HL7702 cells and in MC‐LR‐treated mice' livers owing to the finding that the phosphorylation level of Akt at Thr 308 and Ser 473 was significantly increased.…”
Section: Discussionsupporting
confidence: 66%
“…We found that stimulation with MCLR induced apoptosis in HEK293, possibly through anoikis (Grossmann, ; Wazir et al, ), and that MCLR can promote proliferation through the activation of the Akt/S6K1 pathway in HL7702 (Liu et al, ). Recent studies have demonstrated that MCLR can promote cell invasion and tumor metastasis (Zhang et al, ; Xu et al, ). Xu et al reported that MCLR can promote MDA‐MB‐435 cell invasion and metastasis via the PI3‐K/AKT pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies have demonstrated that MCs may contribute to a higher incidence of primary human carcinomas (Zhou et al, 2002). Experimental evidence also supports that MC-LR may not only act as a tumor initiator, but also stimulate the invasion and migration of cancer cells (Xu et al, 2013; Zhang et al, 2012). It is also documented that MC-LR can promote fibrosis (Milutinovic et al, 2006).…”
Section: Discussionmentioning
confidence: 73%
“…The activation of the PI3K/Akt and MEK/ERK signaling pathways have been suggested to be involved in the apoptosis induced by MC-LR (Wang et al, 2012). Moreover, MC-LR exposure could increase melanoma cell invasion and tumor metastasis as well as EMTbyactivating PI3K/AKT (Tsukamoto et al, 2013; Xu et al, 2013). In addition, it is possible that the activated MAPK signaling pathways play important roles in modulating MC-LR-induced cellular stress responses (Carreras and Poderoso, 2007).…”
Section: Discussionmentioning
confidence: 99%